ANALISIS FILM UPIN & IPIN DALAM PENANAMAN KARAKTER PEDULI SOSIAL - Septyawan, Dony (JURNAL SINEKTIK, 2018)
This research is motivated by the large number of television shows that contain negative content that is often watched by elementary school-age children and animated films upin and ipin which contain the value of social caring character for planting for children in grade III SDB 02 Karangbener. This study aims to determine the value of the character of social care in television shows Upin and Ipin season 5 episode "Ikhlas dari Hati" and the effect on the class III students of SDN 02 Karangbener. This type of research is qualitative. Data collection techniques used are: (1) Interview; (2) Questionnaire; (3) Observation; and (4) Documentation. Based on the result research, it was obtained data that the research conducted on the planting of socially caring character values in class III students showed good results seen from the results of observations and questionnaires. This shows that the animated film upin and ipin season 5 "Ikhlas dari Hati" can be used as a means of planting the social caring character values of the third grade students because in the episode there are many social caring characters that are good for children.